Synthesis and Properties of Pigment Printing Adhesive with Core-Shell Structure for Textiles - Sui*, Zhihui; Pang, Weiwei; Song, Jia; Cao, Xiangyu (Asian Journal of Chemistry, 2013)
Nano-TiO2/polyacrylate emulsion adhesive with core-shell structure was synthesized by seed-emulsion polymerization with methyl acrylate, ethyl methacrylate, butyl acrylate, 2-acrylamide-2-methyl propane sulfonic acid and nano-TiO2 as the main raw materials. Its structure was characterized and performances used as a pigment printing adhesive were discussed. FT-IR spectrum and 1H NMR spectrum analysis showed that copolymerization reaction happened among all kinds of monomers. The core-shell structure of the emulsion adhesive was obviously showed by both DSC test and TEM photograph. The experimental results showed that, compared with the commercial adhesives, the fastnesses of nano-TiO2/core-shell emulsion adhesive were obviously improved. The dry and wet friction fastness could reach level 5, brushing fastness and soaping fastness could be to level 4.